A portrait in poems : the storied life of Gertrude Stein and Alice B. Toklas - Robillard, Evie (Kids Can Press, 2020)
"Poems, paintings and Paris all come to life in this enchanting picture book biography of Gertrude Stein. This story of imagination and expression introduces young readers to Gertrude and her life partner, Alice B. Toklas, who lived in Paris during a fascinating time in history. Divided into short chapters that chronicle different episodes in Gertrude and Alice's life, this book celebrates two women who were full of daring and creativity at a time when women were encouraged to be wives, not writers. Author Evie Robillard's playful second-person free verse and illustrator Rachel Katstaller's charmingly detailed art beautifully capture the lively world of early 20th-century Paris. Young readers will learn about how Gertrude made up her own writing rules. They'll even learn how sitting around "doing nothing, really doing nothing" is a very important part of being a genius! Gertrude's ingenuity and the childlike joy she found in words and ideas are showcased by the inclusion of quotations from her work. Backmatter includes a timeline, resources and an author's note for further learning."--